MOD

( n1 n2 -- n3 )

Divide n1 by n2, giving the single-cell remainder n3. An ambiguous condition exists if n2 is zero. If n1 and n2 differ in sign, the implementation-defined result returned will be the same as that returned by either the phrase >R S>D R> FM/MOD DROP or the phrase >R S>D R> SM/REM DROP.

See:

Testing:

IFFLOORED    : TMOD T/MOD DROP ;
IFSYM        : TMOD T/MOD DROP ;

T{       0       1 MOD ->       0       1 TMOD }T
T{       1       1 MOD ->       1       1 TMOD }T
T{       2       1 MOD ->       2       1 TMOD }T
T{      -1       1 MOD ->      -1       1 TMOD }T
T{      -2       1 MOD ->      -2       1 TMOD }T
T{       0      -1 MOD ->       0      -1 TMOD }T
T{       1      -1 MOD ->       1      -1 TMOD }T
T{       2      -1 MOD ->       2      -1 TMOD }T
T{      -1      -1 MOD ->      -1      -1 TMOD }T
T{      -2      -1 MOD ->      -2      -1 TMOD }T
T{       2       2 MOD ->       2       2 TMOD }T
T{      -1      -1 MOD ->      -1      -1 TMOD }T
T{      -2      -2 MOD ->      -2      -2 TMOD }T
T{       7       3 MOD ->       7       3 TMOD }T
T{       7      -3 MOD ->       7      -3 TMOD }T
T{      -7       3 MOD ->      -7       3 TMOD }T
T{      -7      -3 MOD ->      -7      -3 TMOD }T
T{ MAX-INT       1 MOD -> MAX-INT       1 TMOD }T
T{ MIN-INT       1 MOD -> MIN-INT       1 TMOD }T
T{ MAX-INT MAX-INT MOD -> MAX-INT MAX-INT TMOD }T
T{ MIN-INT MIN-INT MOD -> MIN-INT MIN-INT TMOD }T

ContributeContributions